Reforma jurídica en el código de trabajo en cuanto al recurso de casación y el principio constitucional de oralidad - Ojeda Pasaca, Edwin Patricio (2017)
The selection of the present issue arises given the prevailing and overwhelming need not only workers but also to lawyers in free practice have been powerless to escape the dilatory resulting these processes since they violate rights guaranteed by our Constitution. The legal protected by the Constitution, which refers to the speed and the procedural economy, is flagrantly violated in work processes with the establishment of the appeal in labour cases directly affecting the workers not to observe the principle of orality. In the main provisions of the Constitution of the Republic, as it is that of speed and judicial economy, and that it is work matters, and in particular in these cases justice has to be the most effective and fast possible because it also prevails in these constitutional rights referred to our supreme law, and which concern the protection of the worker , which as I said before is that this dilatory appeal, also violates these constitutionally guaranteed rights. Workers rights are enshrined in the Constitution of the Republic of Ecuador and protected by the State of Ecuador through its different laws; now well many regulations are affecting rights guaranteed in the Constitution and which relate to the protection of the worker, and in the main that refers to the speed and judicial economy, those who should be protected by the State. Now although there are recently reforms to the labour code, but unfortunately in this regard in particular, rather these reforms were aimed at the fact of the proceedings in the trials of job, to ventilation in an oral procedure, on two hearings but raise another important point how the procedural haste is not less true that the Assembly forgot it , and the application in the entire procedure of the labour process, including the appeal. "Article 168.-the administration of Justice, in the discharge of their duties and in the exercise of their functions, shall apply the following principles: 1. the organs of the judiciary shall enjoy independence, internal and external." Any violation of this principle will lead to administrative, civil and criminal liability in accordance with the law. 2. the judiciary shall enjoy administrative, economic and financial autonomy. 3. by virtue of the jurisdictional unit, any other functions of the State authority may perform functions of administration of ordinary justice, without prejudice to the jurisdictional powers recognized by the Constitution. 4. the access to the administration of Justice will be free. The law shall establish the costs regime. 5. in all its stages, judgements and decisions shall be public, except for the cases expressly mentioned in law. 6. the conduct of processes in all matters, instances, stages and proceedings will be conducted using the oral system, in accordance with the principles of concentration, contradiction and device In short a quick effective procedure should be applied, and truthful to ensure faithful compliance with constitutional norms prescribed in our Constitution, in a case as sensitive as they are workers, use and enjoyment of their rights must be fulfilled in its entirety in all and each one of its forms, ensuring always one of the vulnerable groups of society such as that of workers. "The article 169, designated" the procedural system is a measure for the administration of Justice. The rules of procedure enshrined the principles of simplification, uniformity, efficiency, immediacy, speed and judicial economy, and make effective the guarantees of due process. Not be sacrifice justice by single omission of formalities. As causes of this problem include: failure to comply with the constitutional principles such as Celerity, judicial economy and efficiency, the lack of interest of the legislature, the lack of reform in the labour code and related laws related to this legal need. As consequences or effects, nowadays there are many cases in which workers are victims of dilatant judicial processes by their employers and former employers, social problems of their employers, such as non-payment of labor obligations, or wages that do not cover the basic salary unified, i.e. is under the law and as such they are immersed in legal proceedings that are not vented in agile way and in strict compliance with the constitutional principles. So, it is necessary to reform the Labour Code Art.584, in terms of the appeal which is also of oral proceedings, as the entire process. In such a way that a single hearing is set to air the appeal as regards the allegations of the parties, and the Court will give its resolution orally; This procedure will be entirely oral, so it will be agile and efficient. In legal reality as regards the filing of the appeal in labour matters, presents problems that violate the rights of parts of the labor trial, by as to which more than takes more time, wasted resources both State parties. In legal reality as regards the filing of the appeal in labour matters, presents problems that violate the rights of parts of the labor trial, by as to which more than takes more time, wasted resources both State parties